73.2k views
3 votes
Factoring Trinomials in Standard form x^2+2x=-1

User Fsdf Fsd
by
5.5k points

1 Answer

4 votes

Answer:

(x + 1)(x + 1) = 0 OR (x + 1)^2 = 0

Explanation:

First, we need to get the trinomial x^2 + 2x = -1 all on one side of the equation.

x^2 + 2x = -1

x^2 + 2x + 1 = -1 + 1

x^2 + 2x + 1 = 0

Now that the trinomial is on the left-hand side, let's factor the equation.

x^2 + 2x + 1 = 0

(x + 1)(x + 1) = 0

We can simplify this factored trinomial further to be:

(x + 1)(x + 1) = 0

(x + 1)^2 = 0

Cheers.

User Irae Carvalho
by
5.3k points